Metaphors of Mind, Life and Thought in Hamka's Falsafah Hidup (Jurnal Bahasa, 2023)
Humans tend to use metaphors to convey the implicit meaning behind the delivery of literal meaning, especially in writing. The use of metaphors is intended to convey something abstract or explain a complex concept. However, metaphors that contain layered meanings lead to the misinterpretation of meaning. Language users are not able to understand the meaning behind a said expression. This causes the message conveyed by the writer to be misunderstood by the reader, creating ambiguity in meaning and communication failure. In line with that, this study discusses the interpretation of meanings of the metaphors of MIND, LIFE, and THOUGHT in Hamka's book Falsafah Hidup [The Philosophy of Life] based on Hybrid theory and textual analysis. The data for this study was obtained from the first four chapters of Falsafah Hidup. The analysis of these three metaphors has produced several conceptual regions that manifest Hamka's mind in describing the basic dimensions of life. Two forms of metaphor, namely conventional metaphor and linguistic metaphor, have been identified in the study. These two forms of metaphor have also successfully produced three types of conceptual metaphors, namely orientation metaphors, ontological metaphors, and structural metaphors.Keywords: Linguistic metaphor, conventional metaphor, orientation metaphor, ontological metaphor, structural metaphor, Hybrid TheoryFull text: PDF